Improving crop yield potential: Underlying biological processes and future prospects. Issue 1 (2nd December 2022) - Burgess, Alexandra J.; Masclaux‐Daubresse, Céline; Strittmatter, Günter; Weber, Andreas P. M.; Taylor, Samuel Harry; Harbinson, Jeremy; Yin, Xinyou; Long, Stephen; Paul, Matthew J.; Westhoff, Peter; Loreto, Francesco; Ceriotti, Aldo; et al.
Abstract: The growing world population and global increases in the standard of living both result in an increasing demand for food, feed and other plant‐derived products. In the coming years, plant‐based research will be among the major drivers ensuring food security and the expansion of the bio‐based economy. Crop productivity is determined by several factors, including the available physical and agricultural resources, crop management, and the resource use efficiency, quality and intrinsic yield potential of the chosen crop. This review focuses on intrinsic yield potential, since understanding its determinants and their biological basis will allow to maximize the plant's potential in food and energy production. Yield potential is determined by a variety of complex traits that integrate strictly regulated processes and their underlying gene regulatory networks. Due to this inherent complexity, numerous potential targets have been identified that could be exploited to increase crop yield. These encompass diverse metabolic and physical processes at the cellular, organ and canopy level. We present an overview of some of the distinct biological processes considered to be crucial for yield determination that could further be exploited to improve future crop productivity. Abstract : The manuscript is part of a review collection from the CropBooster‐P project (https://www.cropbooster‐p.eu/ ). In this review, we present an overview of some of the distinct biological processes considered to be crucial for yield determination and recent updates in the respective fields. In the future, these could further be exploited to improve crop productivity.